Terapi Komplementer pada Pasien CKD dengan Sleep Disorder - Ratna Esmayanti; Agung Waluyo; Lestari Sukmarini (Jurnal Keperawatan Silampari, 2022)
This study aims to collect sufficient information on the role of complementary therapy in CKD patients with sleep disorders. The method used in this study is a literature study by collecting and reviewing several published articles related to the role, use and effect of complementary therapies in CKD patients with sleep disorders. The results showed the role of providing sleep hygiene training interventions, progressive muscle relaxation therapy, religious relaxation therapy, foot massage therapy and aromatherapy, and acupressure in improving sleep quality in patients. Sleep hygiene training, progressive muscle relaxant therapy, religious relaxation therapy, foot massage therapy and aromatherapy and acupressure can improve the patient's sleep quality. In conclusion, the five complementary therapies were able to improve the sleep quality of CKD patients on hemodialysis. However, from the five therapies above, the authors conclude that dialytic acupressure is the most effective intervention. Keywords: CKD, Complementary, Sleep Hygiene